Comparison of PMF and LEAF as Optical Fibre Stress and Temperature Sensing Elements - Kuja, S.; Boiyo, Kiboi; Waswa, D.; Amolo, G.; Kipnoo, E.K.R.; Gibbon, T.; Leitch, A. (My University, 2013)
We experimentally investigate the sensitivity of PMF and LEAF fibre. The design of a stress sensor gave the best sensitivity of 0.051 kg -1 while that of a temperature sensor, gave the best sensitivity of 0.181 0C1